Nuclear medicine imaging in non-seminomatous germ cell tumors: lessons learned from the past failures - Narjess Ayati; Emran Askari; Maryam Fotouhi; Masume Soltanabadi; Atena Aghaee; Hesamoddin Roustaei; Andrew M. Scott (Cancer Imaging)
Abstract There is an unmet need for a more accurate molecular imaging radiotracer in the field of non-seminomatous germ cell tumors (NSGCT). The clinical problem is that no single imaging modality is able to differentiate teratoma from necrotic tissue in NSGCTs, which the nuclear medicine techniques are no exception. The exponential growth in the list of potentially promising radiotracers may hold promise in the future for imaging of NSGCTs. Here, we have reviewed the past efforts and potential future advances in this field.